Factors Influencing Anxiety of Health Workers During Pandemic Covid-19 - Sri Mumpuni Yuniarsih; Lutfiana Inda Hapsari; Rusdi Rusdi (Universitas Muhammadiyah Semarang, 2021)
The Corona Virus has become a world health problem in early 2020. Coronavirus Disease 2019 (COVID-19) is a disease that has never been previously identified in humans. Health workers who are at the forefront of handling Covid-19 have high psychological disorders, one of which is anxiety. The purpose is to identify the factors that influence anxiety in health workers during the Covid-19 pandemic. The databases used include Google Scholar, PubMed Central and ResearchGate. 528 articles were found based on selected keywords, the number of articles after duplication-checking was 164 articles. Then screening was carried out according to the inclusion criteria (n = 20) and a total of 144 articles were eliminated because they did not match the inclusion criteria. The number of articles following the due diligence test (n = 10) and 10 articles were eliminated because they did not meet the due diligence requirements. Then 10 articles were taken for review. The results showed that the factors that influence anxiety in health workers are gender, age, family status, availability of PPE, knowledge, contact with COVID-19 patients, chronic disease, a physical and psychological workload that threatens the health, cooperation between colleagues, working in an infectious isolation ward. Psychological disorders such as anxiety have long-term impacts and can affect the work efficiency of health workers. If this anxiety is not managed properly, it can affect the performance of health workers in dealing with Covid-19. The most dominant factors affecting anxiety are age, the availability of PPE and concerns about transmission